2017
DOI: 10.35196/rfm.2017.4.491-494
|View full text |Cite
|
Sign up to set email alerts
|

ANATOMÍA Y MORFOLOGÍA DE PLANTAS MICROPROPAGADAS-ACLIMATADAS DE Agave potatorum Zucc. FERTIRRIGADAS EN VIVERO

Abstract: Agave potatorum Zucc. es una especie silvestre, colectada sin planes de manejo, por lo que se propone propagarla in vitro. El objetivo de la investigación fue evaluar las características morfológicas y anatómicas de plantas de A. potatorum micropropagadas-aclimatadas y fertirrigadas con cantidades diferentes de nutrimentos en vivero. Durante los años 2014-2015 se estableció un experimento en vivero, donde 180 plantas micropropagadas-aclimatadas se separaron en seis grupos de 30 plantas para fertirrigarlas dos … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 6 publications
0
3
0
1
Order By: Relevance
“…Moreover, the anatomy and physiology of the genus Agave, together with appropriate greenhouse management, probably contributed to the adequate development of plantlets ex vivo without affecting their survival. Luna-Luna et al (2017) observed that high fertigation during the acclimatization stage ensures the optimal development of A. potatorum plants obtained in vitro.…”
Section: B Amentioning
confidence: 94%
See 2 more Smart Citations
“…Moreover, the anatomy and physiology of the genus Agave, together with appropriate greenhouse management, probably contributed to the adequate development of plantlets ex vivo without affecting their survival. Luna-Luna et al (2017) observed that high fertigation during the acclimatization stage ensures the optimal development of A. potatorum plants obtained in vitro.…”
Section: B Amentioning
confidence: 94%
“…Although not currently listed in any risk category by the Official Mexican Standard NOM-059-ECOL-2010 (SEMARNAT, 2010), A. potatorum may be classified as a species subjected to special protection in the future, given the intensive extraction to which it is currently subjected, its long flowering time to produce seeds (10-30 years) (Blancas et al, 2010;Rangel-Landa et al, 2015), and its nil asexual reproduction. The main alternative for improving agave productivity is the selection, in vitro micropropagation, and the subsequent plantation establishment of elite individuals (Luna-Luna et al, 2017;Aguilar and Rodríguez, 2018;Monja-Mio et al, 2019). However, this approach requires developing efficient species-specific micropropagation protocols.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Generalmente los suelos donde se desarrollan especies del género Agave, son pobres en materia orgánica, N y P (Bautista-Cruz et al, 2007). Estudios previos han revelado efectos positivos de la aplicación de P sobre el crecimiento de agaváceas, variables como altura de planta, número de hojas desplegadas, diámetro de tallo y acumulación de biomasa son las que mejor respuesta han presentado (Martínez-Ramírez et al, 2013;Luna-Luna et al, 2017). El objetivo de este trabajo fue evaluar el efecto de la inoculación con hongos micorrízicos comerciales y la aplicación de diferentes dosis de P sobre el crecimiento y contenido de sólidos solubles totales (SST) de dos agaves silvestres: agave tobalá (Agave potatorum Zucc) y agave coyote (Agave spp.)…”
Section: Introductionunclassified